Worker’s Remittances and GDP Growth in Pakistan - Hussain, Rashid; Anjum, Ghulam Abbas (International Journal of Economics and Financial Issues, 2014)
The worker’s remittances are considering second largest source of finance in developing countries after FDI. Worker’s remittances and GDP growth has analyzed for Pakistan for the period from 1973 to 2011. The Generalized method of moments (GMM) has used to control endogeniety problem and GMM also employed to handle unobservable effects. The study showed that worker’s remittances are positive as well as significant with GDP growth and also playing an active role in Pakistan economy. Impact of financial sector on GDP growth is also positive and significant as trade openness and world growth GDP. The vital policy based on our finding is financial sector should be improve for smooth and horizontal transection of remittances and also this sector perform productive investment. Keywords: remittances; volatility; FDI; GMM; financial development JEL Classifications: E01; F24; F43